Impact of Interface Energetic Alignment and Mobile Ions on Charge Carrier Accumulation and Extraction in p‐i‐n Perovskite Solar Cells - James Durrant (Advanced Energy Materials, 2023)
Understanding the kinetic competition between charge extraction and recombination, and how this is impacted by mobile ions, remains a key challenge in perovskite solar cells (PSCs). Here, this issue is addressed by combining operando photoluminescence (PL) measurements, which allow the measurement of real-time PL spectra during current–voltage (J–V) scans under 1-sun equivalent illumination, with the results of drift-diffusion simulations. This operando PL analysis allows direct comparison between the internal performance (recombination currents and quasi-Fermi-level-splitting (QFLS)) and the external performance (J–V) of a PSC during operation. Analyses of four PSCs with different electron transport materials (ETMs) quantify how a deeper ETM LUMO induces greater interfacial recombination, while a shallower LUMO impedes charge extraction. Furthermore, it is found that a low ETM mobility leads to charge accumulation in the perovskite under short-circuit conditions. However, thisalone cannot explain the remarkably high short-circuit QFLS of over 1 eV which is observed in all devices. Instead, drift-diffusion simulations allow this effect to be assigned to the presence of mobile ions which screen the internal electric field at short-circuit and lead to a reduction in the short-circuit current density by over 2 mA cm−2 in the best device.